Frequency Of Abo Blood Group Alleles Among University Students In Baghdad, Iraq: A Cross-Sectional Study - Ruaa Abdulmahdi Saleh Magsoos; Mohammed M. Mohammed; Musa K. Al-Janabi (American Journal of Biomedicine and Pharmacy, 2026)
Background: Understanding the ABO blood group system could greatly benefit clinical practice as the ABO blood group system is one of the most important genetic variations in the human population. Knowing how common ABO alleles are in particular population groups helps with blood donation services, transfusion related medical care, as well as across most organ transplant programs and for conducting population based health research. Objectives: Our objective was to determine the frequency of ABO blood groups and their alleles, as well as assess whether or not the sample of university students had the Rh(D) antigen, and check to see if their allele frequencies were in Hardy-Weinberg equilibrium (HWE). Methods: A cross-sectional study took place between September 2023 and March 2024 in Baghdad, Iraq. 450 university students in the age range of ~21.1 years (218 males and 232 females children) were recruited using passive means of sample selection. All participants were phenotyped according to ABO blood group type and Rh(D) blood group type using known methods of agglutination (e.g. combining the phosphate buffered sera supply with blood samples) in the laboratory and recording the participant's blood type. Blood grouping used the Bernstein method to calculate the frequency of ABO alleles (using the phenotype of that cohort) and chi-square methods to determine if the ABO alleles were in HWE. Results: In this cohort, O type blood was most common (37.6%), followed by A type blood (29.6%), B type blood (25.1%), and AB type blood (7.8%). The allele frequency of this cohort was i(r)=0.6126; IA(p)=0.2081; IB(q)=0.1793. There was no observed deviation of this cohort's allele frequencies from HWE for the ABO blood group alleles (χ²=1.84; p=0.841). The majority of participants were Rh positive (n=413) and the minority were Rh negative (n=37). No statistically significant difference existed for Rh typing based upon sex of participant. Conclusions: The estimated frequencies of ABO blood group alleles in university students from Baghdad were comparable to previous frequency estimates of blood groups in Iraqi populations and Middle Eastern populations in general. It is of interest because of the relative high frequency of Rh negative blood among Middle Eastern populations compared to East Asian populations. The provided data will serve as a foundation for comparing unit values for blood donation services and future transplant planning in Baghdad.